PEDAGOGICAL MANAGEMENT OF CREATION OF CONDITIONS, WAYS AND APPROACHES TO THE PERSONALITY OF A STUDENT OF PHYSICS - Buryak, V.K.; Reva, Yu.V.; Vernyhora, A.V.; Kovalchuk, L.A. (Pedagogy of Higher and Secondary Education, 2003)
This article deals with the pedagogical government in making conditions, approaches and ways to an individual of a pupil on materials of studying physics.